7m-6m-4m=63

Simple and best practice solution for 7m-6m-4m=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m-6m-4m=63 equation:


Simplifying
7m + -6m + -4m = 63

Combine like terms: 7m + -6m = 1m
1m + -4m = 63

Combine like terms: 1m + -4m = -3m
-3m = 63

Solving
-3m = 63

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '-3'.
m = -21

Simplifying
m = -21

See similar equations:

| x^2-40x-8=0 | | 6b-14=-7-b | | X/2=x/4+6 | | 135=28x-5 | | 3g+3*2-g+4*g+1= | | 1/3+2/5=100 | | 5(x+-3)-2(x-1)=20 | | 123456789*123456789-12345679+123456789/123456789*123456789 | | (6y-2)+4=22 | | 0.04x-3(x+0.4)=1.5 | | 4(x-3)=2(5x-15) | | 5x+8=13-2x | | y*y^5*y^2= | | -2x-5=-8+13 | | 7+3n=n+7 | | -3x+8=8-2x | | (2-3x^2)(x^3+8)= | | -2x-5=-8 | | 3-x=3x-13 | | 9=h/6-4 | | (2-3x^3)(x^3+8)= | | 28x-5+135=180 | | -3(1+2v)-2(v+7)=-65 | | 4+2x=16-2x | | 8x-16=10x-x^2 | | 5/2*4/5 | | 5x^2-20=3x | | 5(2-v)=7v-26 | | [15+(-5)]+6= | | 5x/16+8=-1/8 | | 21=7/3x | | 5/2(4/5) |

Equations solver categories